Physical activity and gender: comparative study between adolescents from Monterrey, Mexico and Zaragoza, Spain. - Ceballos Gurrola, Oswaldo (2009)
The purpose of this study is to compare medium energy expenditure and levels of physical activity between adolescents from Monterrey, Mexico and Zaragoza, Spain taking into consideration variables such as gender, type of school, and time of the week.  Methods: adolescent students of 12 to 17 years of age from public and private schools in Monterrey (N= 396) and Zaragoza (N= 394).  The Four-by-One-Day Physical Activity Questionnaire was used and a .89 reliability with a test-retest because the test was adapted to this study.  Results: In Zaragoza as well as in Monterrey there is a significant number of students with low levels of physical activity.  Almost half of the students have been classified as inactive and very inactive.  The energy expenditure was very similar for both cities: Monterrey 37.52 ± 2.12 kcal/kg/day and Zaragoza 37.66 ± 2.95 kcal/kg/day.  Conclusions: Regarding gender, men show greater levels of physical activity than women.  This data coincides with the majority of the studies.  Students perform a higher level of physical activity during school days than during weekends.